2011
DOI: 10.1017/s002185961100061x
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic simulation of the cost of home-produced feeds for ruminant livestock systems

Abstract: SUMMARYAn agro-economic simulation model was developed to facilitate comparison of the impact of management, market and biological factors on the cost of providing ruminant livestock with feed grown on the farm (home produced feed). Unpredictable year-to-year variation in crop yields and input prices were identified as quantifiable measures of risk affecting feed cost. Stochastic analysis was used to study the impact of yield and input price risk on the variability of feed cost for eight feeds grown in Ireland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
71
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(84 citation statements)
references
References 27 publications
1
71
0
2
Order By: Relevance
“…In Ireland, the cost of conserved grass is frequently lower than that of alternative feedstuffs while grazed grass is the cheapest feedstuff available to producers (Finneran et al, 2011). The inclusion of a conserved grass and/or a grazing period prior to slaughter is desirable from a cost of production perspective.…”
Section: Introductionmentioning
confidence: 99%
“…In Ireland, the cost of conserved grass is frequently lower than that of alternative feedstuffs while grazed grass is the cheapest feedstuff available to producers (Finneran et al, 2011). The inclusion of a conserved grass and/or a grazing period prior to slaughter is desirable from a cost of production perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Dairy production systems that efficiently convert pasture into milk, through maximising grass utilisation, are most profitable, as grazed grass can supply nutrients to dairy cows at a lower cost than alternative feeds in cool temperate regions (Finneran et al, 2012). The greatest opportunities to increase the contribution of grazed grass to the dairy cow diet exist in early spring and late autumn; however, spring grass growth can be extremely variable resulting in deficits in grass supply (McCarthy et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For other compounds such as HMA, Cole and McCroskey (1975) suggested that the level of concentrate supplementation could affect their efficacy as methane inhibitors. The implications of these differences for practical farming systems could be important in countries such as Ireland where grassland is the dominant (~0.9) crop on agricultural land and provides the lowest-cost feed available for ruminant production systems (O'Riordan and O'Kiely 1996;Finneran et al 2012). Concentrate feeds (with grass silage) are fed when livestock are accommodated indoors and these feeds can also constitute a major proportion of the lifetime feeding costs of ruminants (O'Riordan and O'Kiely 1996).…”
Section: Introductionmentioning
confidence: 99%